Business Solutions for Realeyes - Aditya, Katti (2009)
The purpose of this report is to propose business solutions for a start-up firm called Realeyes that provides eye-tracking services in UK, Europe and United States. This report makes use of the research and interview findings from the group project that involved developing an international marketing plan for Realeyes to launch in Australia. However, the recommendations in this report have been made keeping in mind Realeyes’ global operations.